2009
DOI: 10.1017/s0144686x0999016x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with traumatic memories: Second World War veterans' experiences of social support in relation to the narrative coherence of war memories

Abstract: This paper reports a qualitative study that used narrative analysis to explore how social support helps many armed-services veterans cope with traumatic memories. The analysis was carried out on two levels, that of narrative form (level of narrative coherence), argued to be indicative of reconciliation, and narrative content (themes of social support), which allowed exploration of the types of social support experienced by veterans with coherent, reconciled and incoherent narratives. Ten British male Second Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 42 publications
2
54
0
Order By: Relevance
“…Sources of social support included previous military comrades, veterans' associations and wives and family (Hunt and Robbins, 2001b). It highlighted that as veterans aged, they seemed to call on veterans associations more as they started to experience more distress or felt that they had 'more to say' (Burnell, Coleman and Hunt, 2010). By trying to consider the role of time and distance from experience in understanding potentially traumatic events, this work highlighted the effect of ageing on an ex-service population (Hunt and Robbins, 2001a).…”
Section: Coping With Post-service Life As An Older Adultmentioning
confidence: 99%
“…Sources of social support included previous military comrades, veterans' associations and wives and family (Hunt and Robbins, 2001b). It highlighted that as veterans aged, they seemed to call on veterans associations more as they started to experience more distress or felt that they had 'more to say' (Burnell, Coleman and Hunt, 2010). By trying to consider the role of time and distance from experience in understanding potentially traumatic events, this work highlighted the effect of ageing on an ex-service population (Hunt and Robbins, 2001a).…”
Section: Coping With Post-service Life As An Older Adultmentioning
confidence: 99%
“…She found that although most had discussed those experiences with her for the first time in those interviews, they reported relief for having done so but did not continue such discussions with others (e.g., friends or family). Burnell, Coleman, and Hunt (2010) examined narratives of 10 British male World War II veterans regarding their war experiences, traumatic memories, and experiences of social support in an effort to identify ways veterans' friends and family can provide support that will aid in reconciliation of traumatic memories. Other scholars have explored ways veterans manage stress and trauma associated with their service: Buntz (2003) examined the "discourse of trauma" in poetry written by Vietnam War veterans; Michel (2004) studied the reflection of war experiences in artwork created by Vietnam War veterans; and Hopkin (2004, p. 188) examined memoirs written by 18th-and 19th-century French soldiers and sailors to uncover ways they "made sense of their experiences, expressed their understanding to others, and devised strategies to cope with the circumstances of their lives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to those already discussed (Burnell, Coleman, & Hunt, 2010;Parr, 2007), other scholars have used narratives or life stories as a method of analysis in studies of war veterans. Lomsky-Feder (2004) examined the life stories of 63 Israeli men who all served in the Yom Kippur War to explore how memories of war are socially constructed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While previous qualitative studies have examined the complexities of the military experience, and speculated about the effect of the shift from territorial to peacekeeping operations (Ray, 2009), there are no published papers comparing soldiers from both types of conflict. Papers covering the importance of the moral dimension and societal support in trauma adjustment are similarly scarce, although this issue has been raised by specialists in the field (Burnell, Coleman, & Hunt, 2010;Hautamäki & Coleman, 2001;O'Brien & Hughes, 1991;Summerfield, 2002). Indeed, some have proposed that addressing the moral dimension of conflict is an essential part of modern warfare (Lev, 2008).…”
Section: Introductionmentioning
confidence: 97%